Digital coherent transmitter using electroabsorption modulator integrated laser - Mekbungwan P. (2017)
© 2016 IEEE. We investigate the feasibility of an electroabsorption modulator integrated laser as a digital coherent transmitter. The laser and EAM sections are used as phase and amplitude modulators respectively. We discuss the challenges involved and demonstrate the combined phase and amplitude modulation on a commercial device.